The diversity and distribution of residential termites in the Minahasa Raya Region, North Sulawesi Province, Indonesia - JACKLIN STELLA SALOME MANOPPO; RAMADHANI EKA PUTRA; RUDI DUNGANI; INTAN AHMAD (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Manoppo JSS, Putra RE, Dungani R, Ahmad I. 2024. The diversity and distribution of residential termites in the Minahasa Raya Region, North Sulawesi Province, Indonesia. Biodiversitas 25: 39-48. Termites are major pests in urban settings, particularly due to their preference for wood, despite its ecological importance leading to structural damage to buildings. Studies showed a gap in the North Sulawesi Region, Indonesia, particularly in termite distribution, control, and economic impact in residential zones. This study aimed to (i) gather preliminary data on termite species in Minahasa and North Sulawesi from the literature; (ii) locate termite colonies via house/building surveys and baiting; (iii) map the distribution of identified termite species by Geographical Information System (GIS); and (iv) record environmental characteristics relevant to termite distribution and related damages. The study revealed a diversity of residential termite species in terms of morphological characteristics and habitats. Three termite families were identified: Rhinotermitidae, Termitidae, and Kalotermitidae, encompassing five sub-families and six genera, with the most notable species being Cryptotermes brevis Walker 1853, Odontotermes javanicus Holmgren, 1912, and Nasutitermes atripennis Haviland, 1898 among others. The Cryptotermes and Odontotermes were the most commonly encountered genera in Minahasa Raya's residential areas.